Peran Kepala Sekolah sebagai Supervisor dalam Meningkatkan Kualitas Pendidikan di Sekolah Dasar Negeri Sunyaragi 2 Kota Cirebon - Masduki (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
The role of the Principal as Supervisor is to provide guidance, assistance and direction to educators and education staff to facilitate the implementation of the educational process that encourages educational progress. The provision of education requires quality assurance to ensure compliance with or exceed national education standards. The school provides students with high-quality learning services through the use of various technologies. There needs to be teachers who have professionalism, and qualifications and meet the required competency standards. The implementation of educational supervision is expected to improve the quality of education in schools. This research uses a qualitative methodology that examines the state of natural entities. The results of qualitative research prioritize interests above generality. The findings of this research establish that supervision is specifically intended to grow and improve teacher professionalism, thereby facilitating teacher career growth. The aim is to increase the effectiveness and productivity of the educational process. Supervision provides support to instructors in improving the teaching and learning environment. The findings of this study indicate that educational supervision has several roles, including coordination, consultation, and evaluation. The process of implementing supervision is separated into three distinct steps: planning, implementation, and assessment.